Asymptotic formula on average path length in a hierarchical scale-free network with fractal structure. (May 2019) - Zhang, Qian; Xue, Yumei; Wang, Daohua; Niu, Min
Abstract: In this paper, we study a hierarchical scale-free network with special fractal structure. We study the average path length and associate the average path length with the symbol length. Then using a recursive method, we obtain the asymptotic formula for average path length of our networks.